Pengaruh Gaya Kepemimpinan Transformasional Terhadap Kinerja Karyawan Di Perusahaan Startup - Pratiwi, Jeny Eka (Jurnal Ilmu Ekonomi dan Bisnis, 2025)
This study aims to analyze product innovation strategies implemented by Micro, Small, and Medium Enterprises (MSMEs) to enhance competitiveness in the digital era. A descriptive qualitative approach was employed, with data collected through in-depth interviews, field observations, and document analysis involving ten MSME actors in Jakarta, Bandung, and Surabaya. The findings reveal that product innovations include quality improvements, design differentiation, and adaptation to market preferences through the use of digital technology. Digitalization plays a crucial role in accelerating innovation processes and expanding market reach, particularly through social media and e-commerce platforms. However, challenges such as limited digital literacy and restricted access to technology remain significant barriers for some MSMEs. The study concludes that product innovation strategies integrated with digital technology and supported by a conducive ecosystem can sustainably improve MSME competitiveness. These findings are expected to serve as a reference for entrepreneurs, government institutions, and policymakers in promoting innovation-based MSME growth amid digital transformation.